2018
DOI: 10.1002/hed.25426
|View full text |Cite
|
Sign up to set email alerts
|

Early experience of transoral thyroidectomy: Comparison of robotic and endoscopic procedures

Abstract: Background The aim of this study was to evaluate the feasibility, safety, and early surgical outcomes of transoral thyroidectomy and to compare robotic and endoscopic procedures. Methods A total of 37 patients underwent robotic (23 cases) or endoscopic (14 cases) transoral thyroidectomy. We compared the outcomes of the two procedures. Results Of the 37 patients, 2 were converted to the robotic facelift approach as a result of an intraoperative CO2 embolism and inability to remove the tumor. The mean operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…However, most studies of transoral thyroidectomy are case series with relatively small sample sizes, and there are only a few studies involving more than 100 cases . Transoral robotic thyroidectomy is performed in a very limited number of centers, and its surgical outcomes are not well determined. Hence, in this study, we evaluated the safety and efficacy of transoral robotic and endoscopic thyroidectomy in the first 100 patients, focusing on safety and complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most studies of transoral thyroidectomy are case series with relatively small sample sizes, and there are only a few studies involving more than 100 cases . Transoral robotic thyroidectomy is performed in a very limited number of centers, and its surgical outcomes are not well determined. Hence, in this study, we evaluated the safety and efficacy of transoral robotic and endoscopic thyroidectomy in the first 100 patients, focusing on safety and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Transoral thyroidectomy includes the sublingual approach and the oral vestibular approach, as well as other modifications with or without CO 2 insufflation . The oral vestibular approach has been the most popular recently, and transoral robotic and endoscopic thyroidectomy has been found to be feasible and safe in properly selected patients . Also some studies have compared the transoral and conventional transcervical approaches, and reported similar outcomes in the two .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the various remote access thyroidectomy procedures, the transoral vestibular approach, using endoscopy or a surgical robot, has been popularized and adopted worldwide due to its decreased surgical morbidity and superior cosmesis 1‐8 …”
Section: Introductionmentioning
confidence: 99%
“…We have performed robotic and endoscopic surgery for the thyroid, parathyroid or submandibular glands, as well as branchial cleft cysts and other neck masses, since 2005, using transaxillary, postauricular facelift and transoral approaches [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%